Clinical Approach to Inconclusive Subscapularis Tear Diagnosis: a Meta-analysis - Wang, Hao; Cao, Xiangyu; Li, Baoqiang; Ning, Taiguo; Cao, Yongping (International Journal of Sports Medicine, 2023)
To identify factors associated with subscapularis (SSC) tears and provide a theoretical basis for clinical diagnosis, we included studies related to subscapularis tears published before February 1, 2023. We screened for six predictors across previous studies for the meta-analysis. The predictors included age, sex, coracoid overlap (CO), coracohumeral distance (CHD), impairment of the long head of the biceps tendon (LHB), and dominant arm. The Newcastle-Ottawa Scale (NOS) was used to evaluate the quality of the studies. The risk ratios (RRs) and the weighted mean differences (WMDs) were used to evaluate the effect size of categorical variables and continuous variables, respectively. The Egger test was used to assess the publication bias of the studies. Ten studies were included from seven countries. A total of 2 126 patients were enrolled, of whom 1 041 had subscapularis tears and 1 085 did not. The study showed that age (WMD, 4.23 [95% CI, 2.32–6.15]; P<.00001), coracoid overlap (WMD, 1.98 [95% CI, 1.55–2.41]; P<.00001), coracohumeral distance(WMD, –1.03 [95% CI, –1.17– –0.88]; P<.00001), and an injury of the long head of the biceps tendon (RR, 4.98 [95% CI, 3.75–6.61]; P<.00001) were risk factors for subscapularis tears. These risk factors can help clinicians identify subscapularis tears early and select appropriate interventions. The level of evidence is 3.
Keywords: risk factor; subscapularis tear; coracohumeral distance; long head of biceps tendon injury; coracoid overlap